2014
DOI: 10.1371/journal.pone.0092206
|View full text |Cite|
|
Sign up to set email alerts
|

The Impact of Policy Guidelines on Hospital Antibiotic Use over a Decade: A Segmented Time Series Analysis

Abstract: IntroductionAntibiotic pressure contributes to rising antibiotic resistance. Policy guidelines encourage rational prescribing behavior, but effectiveness in containing antibiotic use needs further assessment. This study therefore assessed the patterns of antibiotic use over a decade and analyzed the impact of different modes of guideline development and dissemination on inpatient antibiotic use.MethodsAntibiotic use was calculated monthly as defined daily doses (DDD) per 100 bed days for nine antibiotic groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…Similar rate of adherence to guidelines was observed in a number of previous studies (Abbo et al, 2011;Chandy et al, 2014;Alweis et al, 2014). Adherence to guideline could not be measured in the department of Surgery as very few diagnoses mentioned in the treatment sheet were present in the antimicrobial guideline.…”
Section: Discussionsupporting
confidence: 77%
“…Similar rate of adherence to guidelines was observed in a number of previous studies (Abbo et al, 2011;Chandy et al, 2014;Alweis et al, 2014). Adherence to guideline could not be measured in the department of Surgery as very few diagnoses mentioned in the treatment sheet were present in the antimicrobial guideline.…”
Section: Discussionsupporting
confidence: 77%
“…The majority of the studies that reported significant cost savings did not provide the cost of implementing the program. Table 2 summarizes studies [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] that assessed the impact of ASP on antimicrobial use and cost of antimicrobials.…”
Section: Resultsmentioning
confidence: 99%
“…This apparent difference in trend marks two time segments, period 1 and period 2, best captured by a segmented regression model with the break point at 2003, in combination with harmonic terms describing the cyclic seasonal pattern of counts represented by the Poisson distribution. Thus, we defined the segmented Poisson harmonic regression model [35] in equation 4: ln(E[Y(t)])=βinter+βtrendp1tp1+βcosp1cos(2πωtp1)+βsinp1sin(2πωtp1)+βtrendp2tp2+βcosp2cos(2πωtp2)+βsinp2sin(2πωtp2)+ε , where Y(t) is disease incidence at month t ; β inter is the intercept reflecting counts at the break point (T break ); β trend are the coefficients for trend with t p1 and t p2 representing time in month before and after T break , respectively; similarly β cos and β sin are the coefficients of the harmonic terms for each of two segments or time periods, p1 and p2 , respectively; ω = 1/M, where M=12 is the length of the annual cycle in month; and ε is an error term.…”
Section: Methodsmentioning
confidence: 99%